Analisis Faktor-Faktor yang Memengaruhi Pengungkapan Key Audit Matters di Indonesia - Qadrina, Mahadmi Fattahaulia; Raharja, Surya (Jurnal Ilmiah Wahana Akuntansi, 2024)
This research aims to examine the influence of auditor type, auditor gender, frequency of audit committee meetings, financial expertise of audit committee, independent commissioners, and executive compensation on the disclosure of Key Audit Matters (KAM). The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2022. The sample for this study was selected using purposive sampling method with total of 118 manufacturing companies. The method of analysis used in this research is multiple linear regression analysis. The results indicate that the frequency of audit committee meetings has a positive influence on KAM disclosure. Meanwhile, auditor type, auditor gender, financial expertise of audit committee, independent commissioners, and executive compensation do not significantly influence KAM disclosure.